Proposal to obtain the optimal sample size of pests with an excess of zeros - Otero-Prevost, Luis Gabriel; Villanueva-Jiménez, Juan A.; Ramírez-Valverde, Gustavo; Vargas-Mendoza, Mónica C.; Becerril-Pérez, Carlos M.; Soto-Rojas, Lauro (Revista Mexicana de Ciencias Agrícolas, 2024)
In sampling of pests with low densities, it is common to obtain a large number of zeros, which is difficult to manage since the Poisson and negative binomial probability distributions are not suitable for modeling and equations to estimate the optimal sample size are not available. In this study model the excess of zeros by estimating parameters through the methods of moments and maximum likelihood of the zero-inflated Poisson and zero-inflated negative binomial distributions, and to derive equations to calculate the optimal sample size. Systematic sampling was used to select 100 trees per grove of Río Red grapefruit (Citrus paradisi Macfad) at Finca Sayula, Veracruz, Mexico (latitude 19.20722, longitude -96.35194), from June to July 2021 and January 2022. The number of leafminers (Phyllocnistis citrella Stainton) and aphids (Toxoptera citricida Kirkaldy) present in three leaves per shoot per tree, considered as a sample unit, was counted. Simulations were performed in RStudio with different proportions of zero (0.1, 0.4, and 0.6) to compare the parameters obtained in the field using the methods of moments and maximum likelihood. Equations were derived to estimate the optimal sample size in studies of pests with low densities, based on the zero-inflated Poisson and zero-inflated negative binomial probability distributions. The method of moments yields optimal sample sizes smaller than those obtained by maximum likelihood, because they distinguish the origin from zero, so its use is recommended.
Keywords: sampling; zero-inflated negative binomial; zero-inflated Poisson